Acoustic emission in PZT ceramic in poling process - ALEKSIEJUK, M. (Archives of Acoustics, 2000)
Results of measurements of acoustic emission in PZT type ceramic in strong alternating electric field are presented. Measurements were performed with Sawyer-Tower experimental setup for poling of polarisation of these ceramic materials. Obtained signals of acoustic emission were submitted to spectrum analysis. To the interpretation of spectrum the statistical theory of noise with interactions between events was applied. Time interval parameters applied to the description of domain walls hops were found for the investigated ceramic materials.